A study of lymphocyte subsets, activation markers and herpers viruses infection in epileptic patients in HUSM - Ab. Hamid, Wan Zuraida Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Epilepsy is a chronic brain disorder that affects more than 50 million people throughout the whole world. The cause of more than half of the sufferers remains unknown (idiopathic), while the rest may have epilepsy due to certain causes of head injury, stroke, drugs withdrawal or other identifiable problems. The prevalence of this disease increases annually persuading researchers to find out the possible relations to these idiopathic epilepsies. Previous reports suggested that there could be some kind of association between virus infection and lymphocyte-mediated immunity leading to seizures and therefore this study is conducted 1) to compare mean of lymphocyte subsets between epileptic patients and healthy controls, 2) to compare mean of activated C04+ and cos• T cell subsets between epileptic patients and healthy controls, 3) to determine the sociodemographic factors and lymphocyte subsets in epileptic patients and 4) to observe the associations between lgG, lgM in herpes viruses with lymphocyte subsets In epileptic patients. A total of 190 subjects were enrolled in this study, 95 subjects for each group of healthy controls and epilepsy patients. Subjects recruited fulfilled the inclusion and exclusion criteria. Whole blood and serum samples were tested by flow cytometry and indirect ELISA technique. Statistical analyses were performed using the SPSS version 12.0. Results revealed that the number of NK cells (C016•s6•) were significantly higher in epileptic patients (95%CI: -0.141,-0.002; p value: 0.042) while the number of activated T cells (cos•co2s•) were significantly lower (95%CI: 0.034, 0.222; p value: 0.008) compared to healthy controls. Patient education level (OR: 0.227; 95%CI: 0.127; 0.404; p value: 0.001), the number of C016.56+ (OR: 8.759; 95%CI: 1.643; 46.685; p value: 0.011) and the number of co4•co2s• (OR: 0.229; 95%CI: 0.092 ;0.571; p value: 0.002) were the only parameters that were significantly associated with epilepsy. No significant correlation observed between lymphocyte subsets and herpes viruses infection, however Cytomegalovirus (CMV) lgG shows a significant difference in epileptic patients as compared to healthy controls (p <0.001). This study may suggest that the divergence in NK cells and activated cos• T cells (Cos•co2s•) provides the idea that epilepsy patients has an immune disorder, whereas, previous CMV infection may play a great role in contributing to epilepsy.